Physical exercises in cervical mobility in adults and elderly people: a systematic review (Revista Brasileira Multidisciplinar, 2026)
Changes in cervical mobility not only affect the ability to perform simple movements, but also limit more complex functions that disable postural control and balance and generate widespread impacts. The objective of this work was to systematically review studies in the literature that address the therapeutic potential of physical exercises focusing on the mobility of the cervical spine in adults and elderly people. A systematic literature review was carried out with a bibliographic survey of texts published between 2019 and 2024 in indexed databases such as PubMed, LILACS, SciELO and with the descriptors: “Exercise AND Elderly OR Aged AND neck OR cervical vertebrae AND cervical mobility” interspersed by Boolean operator “AND” and “OR”. By defining the terms of inclusion and exclusion, eighty studies were selected, five of which met the proposal of this review. Studies suggest that physical exercise had positive effects in which pain reduction, increase in cervical range of motion, improvement in neck disability and muscular resistance were the most beneficial outcomes. There were few studies that described the effects of physical exercise on cervical mobility, one of which was associated with elderly people. This research found high variability in the methodologies, duration and intensity of the exercises studied. This limits direct comparisons and makes conclusions about the effectiveness of protocols difficult. Future studies can standardize interventions and expand samples for more robust comparisons between different types of exercise.
Keywords: physical exercises; cervical Mobility; elderly; adults